Exploring the quintessential influence on shadows of black holes in Finsler-Hayward geometry - Manjunath Malligawad; S.K. Narasimhamurthy; Z. Nekouee (Physics Letters B, 2024)
This research aims to shed light on how the quintessential dark energy influences the shadows cast by black holes by considering different kinds of surrounding accretion profiles within the framework of Finsler-Hayward geometry. We explore the impact of the Finsler parameter (η) and the quintessence parameter (ω) on fundamental properties of the black hole, such as its horizons, photon sphere, and impact parameter. By examining the observed characteristics of the black hole's shadow, including the photon ring and shadow intensities, we analyze how the quintessence affects these features under varying scenarios of matter accretion. Leveraging observational data from the Event Horizon Telescope, exclusively focusing on celestial bodies such as Sgr A* and M87*, we narrow down the range of the Finsler parameter (η) within our model of quintessence-infused Finsler Hayward black holes. By comparing our findings with models such as Finsler Schwarzschild, with and without the quintessence Finsler Hayward black holes, we observe that the quintessence's influence on the black hole's shadow surpasses the effects attributed to regularity. This study contributes to our insight into how the Finsler parameter and the quintessence of dark energy shape the shadows of black holes in diverse accretion environments, shedding light on their intricate nature and behavior, particularly in the context of Finsler Hayward geometry.